Bad for business: the construction of modern slavery and the reconfiguration of sovereignty. Issue 1 (21st March 2022) - Fudge, Judy
Abstract: Although the UN calls on governments to end modern slavery, Walk Free, a private foundation connected to the faith-based abolitionist movement, leads the private-public network to eliminate slavery from transnational supply chains. Examining the network's governance techniques reveals how scale and governance are reconfiguring sovereignty beyond the territory of the nation state and aligning it with neoliberal governmentality.